Analisis Sikap dan Minat Beli Konsumen terhadap Produk Fashion dengan Menggunakan Brand Image Merek Lokal dan Impor - Folia, Azella Dwi; Yulianti, Riri Aryani (Applied Business and Administration Journal, 2023)
This research intends to examine customer perceptions and purchasing intentions regarding fashion goods that include both domestic and foreign brand imagery. The causal approach used in this quantitative study examines the strength of correlations between variables by putting preexisting assumptions to the test. Purposive sampling methods were used using smartPLS 3.0 software to choose the sample for this research, which consisted of 100 respondents, utilizing the questionnaire method for data collection. According to the study's findings, donning clothing with a local brand image makes most locals feel prouder and more at ease. They often visit local fashion product stores because they are drawn in by the growth of local brand image models. However, some of them really like purchasing imported fashion items because they believe that, despite the lower price, they are more qualified and distinguished.